Pemanfaatan Air Limbah Domestik Terolah Fasilitas Umum Pendidikan untuk Penyiraman Tanaman - Muhammad Abdus Salam Jawwad; Sarah Aulia (Prosiding ESEC, 2023)
This public educational facility was initiated by a foundation X. This foundation produces domestic wastewater from educational activities, toilets, prayer rooms, canteens, and so on. Domestic liquid waste generated will be used for watering plants in green open spaces around the foundation. The waste water discharge before being treated at WWTP is 17.18 m3 /day and the wastewater discharge after being processed is 17.1167 m3 /day. The entire treated wastewater discharge will be used to water the garden. Wastewater contains BOD, COD, TSS, Ammonia and Total Coliform which exceeds the quality standard, so it needs to be processed before it is used for watering plants. Yayasan X already has 5 WWTP units to manage wastewater. However, it is planned that there will be a building development, so an additional unit of WWTP will be carried out in the building development area so that an evaluation is carried out on the processing capability and the watering method used. The results of the processing will be used to water plants at Foundation X with an area of 1,339.20 m2 of Green Open Space. The process of watering is done two times a day in the morning and evening.